2019
DOI: 10.4314/ovj.v9i1.13
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of infectious bronchitis in layer birds in Plateau state, north central Nigeria

Abstract: A flock of 54 wk-old layer birds exhibiting signs of respiratory distress, greenish diarrhea, and drop in egg production was investigated. A marked drop in egg production (55%) was recorded with eggs appearing white and soft-shelled. Mortality was in the range of 1%–2% with post-mortem lesions revealing cloudy air sacs, frothy, and congested lungs. Viral RNA was extracted from pooled tissue samples (trachea, lungs, spleen, and liver) and tested for Avian influenza virus (AIV), Newcastle disease virus (NDV), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…The finding of high distribution of the Mass serotype with 89.3% across the four Local Government Area in this study supported that of Fellahi et al (2015) who showed that Mass seemed to be the highest in prevalence in a lot of countries when compared to other serotypes given that it was both the first detected and most frequently detected IBV genotype (Fellahi et al, 2015). In commercial poultry, Mass has been identified as the commonly used serotype for vaccination (Shittu et al, 2019). In North America, the commonly used serotypes in most vaccination programs are the Mass, Conn and the Ark (Butcher et al, 2014).…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…The finding of high distribution of the Mass serotype with 89.3% across the four Local Government Area in this study supported that of Fellahi et al (2015) who showed that Mass seemed to be the highest in prevalence in a lot of countries when compared to other serotypes given that it was both the first detected and most frequently detected IBV genotype (Fellahi et al, 2015). In commercial poultry, Mass has been identified as the commonly used serotype for vaccination (Shittu et al, 2019). In North America, the commonly used serotypes in most vaccination programs are the Mass, Conn and the Ark (Butcher et al, 2014).…”
Section: Discussionsupporting
confidence: 83%
“…The findings of this present study revealed the first detection of Conn, Ark and De-072 strains of IBV in free-range chicken in Nigeria. Even though, they had been detected in commercial poultry (Shittu et al, 2019). The prevalence of Conn (5.0%) in Mangu LGA is comparable to the cumulative prevalence (13.4%) reported in the USA from field samples collected during 11 year period occurring throughout the South eastern USA states including North Carolina, Tennessee, Alabama and other Midwest and Western USA states (Jackwood et al, 2005).…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…Molecular and serological surveys in the backyard and commercial poultry flocks have reported IBV variants in the Mediterranean basin and Western and Northern African countries [ 27 , 53 ], but epidemiological and genomic data on IB and its impact on the poultry industry in Africa are scarce. This is despite IBV being one of the most common and important viral agents associated with respiratory disease and severe reduction in egg production in chickens, with IB outbreaks occurring in commercial and backyard flocks regardless of their vaccination status [ 54 ]. Contributing factors to this situation include a lack of surveillance initiatives for poultry viruses and inadequate genomic sequence data of detected isolates, most of which remain uncharacterized.…”
Section: Discussionmentioning
confidence: 99%